2020
DOI: 10.24018/ejfood.2020.2.6.145
|View full text |Cite
|
Sign up to set email alerts
|

Economics and Technical Efficiency of Maize Production Among Small Scale Farmers in Abuja, Nigeria: Stochastic Frontier Model Approach

Abstract: This study evaluated Economics and Technical Efficiency of Maize Production Among Small Scale Farmers in Abuja, Nigeria; Stochastic Frontier Model Approach; Multi-stage sampling technique was adopted and used. Primary data were collected through the use of well-structured questionnaire from one hundred and fifty (150) sampled respondents in the study area. Data were analyzed to achieve the specified objectives using the following tools of analysis, Descriptive Statistics, Stochastic Frontier, Gross Margin Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
4
5
1
Order By: Relevance
“…Education level of a farmer could determine how efficient the farmer would be, especially in the area of resource utilization which could lead to output and profit maximization. This result is in line with (Alabi et al, 2020 andEbukiba et al, 2020) who reported that education is an important factor that can influence small-scale farmers to adopt new innovations and research findings related to their area of production. When a farmer is educated, there is high probability that he will take advantages of innovations and new technologies easily which would eventually lead to improved yield and increase in output.…”
Section: Socio-economic Characteristics Of the Sampled Respondents In...supporting
confidence: 89%
“…Education level of a farmer could determine how efficient the farmer would be, especially in the area of resource utilization which could lead to output and profit maximization. This result is in line with (Alabi et al, 2020 andEbukiba et al, 2020) who reported that education is an important factor that can influence small-scale farmers to adopt new innovations and research findings related to their area of production. When a farmer is educated, there is high probability that he will take advantages of innovations and new technologies easily which would eventually lead to improved yield and increase in output.…”
Section: Socio-economic Characteristics Of the Sampled Respondents In...supporting
confidence: 89%
“…Farm size is considered as a proxy in production as the size of the farm land expands will lead to increase in the total output of soybeans in the study area. This is in consonance with [21] and [32] who indicated positive effect of farm size on the output of soybean, they reported that an increase in farm size will results in increase in the total output of soybean. The coefficient fertilizer influence soybean output negatively and was statistically significant at (P<0.05) probability level the coefficient of fertilizer (-1.691) implies that a percentage change in the quantity of fertilizer applied to the soybean farm will results in the 1.69% decrease in the total output of soybean in the study area this findings is contrary to the apriori expectation and the economic theory, this could be because farmers wrongly applied the fertilizer or the soybean itself doesn't require fertilizer because it has the ability to fix nitrogen into the soil, this result is not consistent with [12] who reported positive relationship between fertilizer and output of soybean implying that an increase in fertilizer usage will result in increase in total output of soybean.…”
Section: Factors Influencing the Total Output Of Soybeans In The Stud...supporting
confidence: 81%
“…The following type of financial ratios was applied in this study in order to determine the profitability of soybean production by farmers as used by [21] and [22]. This was used to achieve part of specific objective two (ii):…”
Section: G Financial Analysismentioning
confidence: 99%
“…Some farms may be operating significantly below the average efficiency level, indicating potential areas for improvement. This result on mean TE is in higher than the 0.620 reported in Umaru and Maurice (2019) and little lower than the 0.950 reported in Ebukiba et al (2020) [26] .…”
Section: Technical Efficiency (Te)contrasting
confidence: 55%
“…Afolami and Faleye (2020) [6] as well as Kalu and Mbanasor (2023) [32] delved into the adoption dynamics of CSAPs, revealing that farm size, age, access to credit, education level, and ownership of means of transport are influential factors. Ebukiba et al (2020) [26] conducted a study focusing on maize productivity, finding a mean technical efficiency (TE) value of 0.950, indicating a high level of efficiency in their sample. Abubakar and Onwujioba (2023) explored various efficiency metrics, reporting mean efficiencies of 97.5% for TE, 46.5% for allocative efficiency (AE), and 45.0% for economic efficiency (EE).…”
Section: Statement Of the Problemmentioning
confidence: 99%